2020
DOI: 10.18203/2394-6040.ijcmph20204743
|View full text |Cite
|
Sign up to set email alerts
|

Association of transfusion transmitted infections with ABO and Rh D blood group system in healthy blood donors: a retrospective analysis

Abstract: Background: Transfusion transmitted infections (TTIs) involves several adverse consequences. Studies have shown that ABO blood groups have some association with various infectious and non-infectious diseases. Few blood groups even can act as a receptor and ligand for infectious agents. The objective of the study was to find out any significant association of TTIs with various ABO and Rh D blood group system.Methods: This retrospective study was conducted from July 2016 to October 2018. Blood donors’ blood was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 12 publications
2
17
3
Order By: Relevance
“…Comparable to Heyredin et al [28], we observed that TTIs were highest in farmers, followed by drivers, and then students and employees. In this study, the frequency of anti-HIV1/2 was higher (4.40%) in the donors of blood group A−ve (p = 0.238), which is analogous to Prakash et al [38]. Interestingly, the highest rate of TTIs and anti-T.pallidum (p = 0.004), in addition to the higher seropositive percentage of more than one marker (p = 0.519), was detected in donors of the AB+ve blood group.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Comparable to Heyredin et al [28], we observed that TTIs were highest in farmers, followed by drivers, and then students and employees. In this study, the frequency of anti-HIV1/2 was higher (4.40%) in the donors of blood group A−ve (p = 0.238), which is analogous to Prakash et al [38]. Interestingly, the highest rate of TTIs and anti-T.pallidum (p = 0.004), in addition to the higher seropositive percentage of more than one marker (p = 0.519), was detected in donors of the AB+ve blood group.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding the screening, the overall seropositive rate of TTIs was 22.52%, which is higher than previous studies [8,[15][16][17][19][20][21][22][27][28][29][30][31][32][33][35][36][37][38]. It is also higher than studies performed in other states of Sudan [13,34,39], as well as a study [11] conducted in our study area formerly.…”
Section: Discussioncontrasting
confidence: 71%
See 3 more Smart Citations